Rancang Bangun Alat Deteksi Penyusup Menggunakan Kamera, Raspberry PI 4 Model B dan OpenCV 4 - Slamet, Rifai; Rakhmadi, Frida Agung; Awaludin, Lukman (Prodi Fisika Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2021)
This research was motivated by the absence of an intruder detection device capable of processing images using OpenCV 4. This study aimed to design and manufacture an intruder detection device using a camera, Raspberry Pi 4 Model B, and OpenCV 4. This research was conducted in 2 stages, namely designing and manufacturing intruder detection device. The design of the device was carried out using the Sketchup 2018 software. The making of this device was carried out in 3 processes, namely making hardware, making dataset, and making software.